EVALUASI PEMBELAJARAN DARING PADA MATA PELAJARAN BAHASA INDONESIA DI SMK MUTIARA KEBUMEN - Kurniawan, Muh. Akbar; Handoko, Omby Ramdhan Wiji; Susanto, Ari (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
The pandemic pushed government to issue implement policies the study in Indonesia which is that learning must be performed online or long distance. This research is aimed to describe the online learning performance of Indonesian language subject during the Covid-19 pandemic at Mutiara Vocational High School of Kebumen. It belongs to a kind of qualitative research, which describe all forms of actions and the phenomena performed by subject examined in the implementation of online learning. The technique of data collection in this research used observation, interviews and documentation. The results of this research illustrated that the performance of online learning in Mutiara Vocational High School of Kebumen at Indonesian language subject reasonably well done, both learners and teachers have had basic facilities what is needed. It described the readiness to perform online learning. In the implementation of online learning, teachers have already done the lesson plan and performed good learning using the learning media, strategies, learning methods and learning approaches are adjusted with the student. Online learning had flexibility in practice and be able to encourage the teachers to be more creative in teaching. Furthermore, students are required to be more self-reliant and motivated to be more active study. However, online learning had a constraints in the implementation of conditions unstable networks and learners' difficulties understood the learning materials is the unique challenge of learning online in Indonesian language subject. Keywords: Evaluation, Online Learning, Covid-19, Indonesian language subject